Potentials of Water Harvesting in the Dry Reions - Singh, S D (Annals of Arid Zone, 2016)
The paper briefly describes basic needs, potential Sill’S, systems design, production potential, and future research and development opportunities of the water harvesting technology. Studies carried out for six years at Jodhpur revealed that runoff, for catchmnent to cultivated area ratio of 0.5, varied from 38 to 68% of the growing season rainfall. Each hectare of the cultivated area thus received 140 to 636 mm of rainfall although the actual rainfall was 117 to 528 mm in different years. As a result, runoff concentration technology facilitated cropping under otherwise too dry a condition for agriculture, lead to increased and stabilised yields, lowered the risk of crop failures and saved production inputs. The total production from two-thirds cropping of a unit area (one-third going to the microcatchment) by runoff farming was the same as from the conventional cropping under flat surface control.